2007
DOI: 10.1525/sop.2007.50.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Jewish Educational and Economic Success in the United States: A Search for Explanations

Abstract: Jews are much more successful economically and educationally than other ethnic, racial, and religious groups in the United States. This article asks why. It begins with a description of how well Jews do and then presents four potential explanations: human capital, Jewish particularity, marginality, and social capital. Most work attempting to explain Jews' success tests human capital explanations. They account for much of Jews' success but leave much unexplained as well. Researchers speculate about the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 73 publications
1
42
0
Order By: Relevance
“…Affiliation is the religious denomination or tradition with which an individual is associated. In the United States, persuasive evidence shows that members of religious groups behave similarly in consequential ways (Burstein 2007;Glass and Jacobs 2005;Keister 2008;Lehrer 2009;Smith and Faris 2005). A long history of research shows that affiliation with mainline Protestant, conservative Protestant, black Protestant, Roman Catholic, Jewish, or other religious groups affects wellbeing (Herberg 1983).…”
Section: Religion and Social Stratification: Two Levels Of Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Affiliation is the religious denomination or tradition with which an individual is associated. In the United States, persuasive evidence shows that members of religious groups behave similarly in consequential ways (Burstein 2007;Glass and Jacobs 2005;Keister 2008;Lehrer 2009;Smith and Faris 2005). A long history of research shows that affiliation with mainline Protestant, conservative Protestant, black Protestant, Roman Catholic, Jewish, or other religious groups affects wellbeing (Herberg 1983).…”
Section: Religion and Social Stratification: Two Levels Of Aggregationmentioning
confidence: 99%
“…The cultural understandings that accompany religious beliefs can influence well-being through demographic behaviors that facilitate or impede human capital acquisition, career advancement and other work behaviors and outcomes, income, and wealth ownership. Religion affects orientations toward education, the attainment of formal education, and the acquisition of other types of training, experience, and expertise (Burstein 2007;Darnell and Sherkat 1997;Glass and Jacobs 2005;Lehrer 1999b). Religion influences sexuality and fertility, including the onset of sexual activity, age at first birth, and family size (Lehrer 1996a;Marcum 1981;Sherkat and Darnell 1999).…”
Section: Micro Model: Mechanismsmentioning
confidence: 99%
“…American Jews' distinctively high secular achievement has long been recognized (Smith, 2005). Several explanations for this have been offered: human capital (e.g., education, long work hours); cultural capital (e.g., placing a high value on education and achievement); social capital (e.g., networking among Jews); and marginality (a motivator of creativity) (Burstein, 2007). However, as Jews have become more integrated into American life ("white," per Brodkin, 1999), their marginality has become increasingly part of the cultural legacy rather than an everyday experience; and their cultural particularity has become less self-conscious and salient, so much so that a sizable minority (about 20%) that others would term "Jewish" do not identify themselves as such (United Jewish Communities, 2003c).…”
Section: Egalitarianism Has Become So Pervasive and Normative In Amermentioning
confidence: 99%
“…By focusing on this relationship, we address the question of whether investment in Jewish "cultural capital," "religious capital," "ethnic capital," or "social capital" might be related to patterns of secular achievement. The literature that has linked the high educational and occupational achievement of Jews to "cultural particularity" and Jewish social networking (summarized in Burstein, 2007) suggests that there is a link between at least certain aspects of Jewish identity and educational and economic achievement. Hurst and Mott (2006) suggest that men and women who have "moderate" Jewish religious connections and behaviors (as opposed to connections that are extremely particularistic or observant, on the one hand, or extremely secular, on the other) have higher secular achievement.…”
Section: H a P T E Rmentioning
confidence: 99%
“…However, religious identity for most people in the UK remains important, at least to the extent that they select a particular religious category in the census and the other official surveys whenever the question about religious affiliation is present. Furthermore, evidence from the US, Canada and the UK suggests that religion is significantly related to labour market outcomes (Brown, 2000;Burstein, 2007;Chiswick & Huang, 2008;Khattab, 2009;Khattab & Johnston, 2013;Meng & Sentance, 1984;Model & Lin, 2002;Steen, 1996). These studies have revealed significant labour market differences between various religious groups and denominations.…”
mentioning
confidence: 99%